Формулы по тригонометрии

Формулы по тригонометрии

Файл : SIN&COS.DOC (размер : 34,816 байт)

cos(=((1-sin2(=(1-tg2(/2)/(1+tg2(/2)

sin(=((1/1+ctg2(=(2tg(/2)/(1+tg2(/2)

cos((()=sin(sin(cos(cos(

sin(((((=sin(cos((sin(cos(

tg((+()=sin((+()/cos((+()=(tg(+tg()/(1-tg(tg()

tg((-()=(tg(-tg()/(1+tg(tg()

ctg((+()=(ctg(ctg(-1)/(ctg(+ctg()

ctg((-()=(ctg(ctg(+1)/(ctg(-ctg()

sin2(=2sin(cos(=(2tg()/(1+tg2()

cos2(=cos2(-sin2(=(1-tg2()/(1+tg2()=2cos2(-1=1-2sin2(

tg2(=2tg(/(1-tg2()ctg2(=(ctg2(-1)/2ctg(

ctg2(=(ctg2(-1)/2ctg(

cos2(/2=1+cos(/2cos2(=(1+cos2()/2

sin2(/2=1-cos(/2sin2(=(1-cos2()/2

cos(/2=((1+cos(/2

sin(/2=((1-cos(/2

tg(/2=((1-cos(/1+cos(=(sin()/(1+cos()=(1-cos()/sin(

ctg(/2=((1+cos(/1-cos(=sin(/(1-cos()=(1+cos()/sin(

sin(+cos(=(2 cos((/4-()

sin(-cos(=(2 sin((-(/4)

cos(-sin(=(2 sin((/4-()

cos(+cos(=2cos((+()/2cos((-()/2

cos(-cos(=-2sin((+()/2sin((-()/2

sin(+sin(=2sin((+()/2cos((-()/2

sin(-sin(=2sin((-()/2cos((+()/2

tg((tg(=(sin(((())/cos(cos(

cos(cos(=1/2(cos(((()+cos((+())

sin(sin(=1/2(cos(((()-cos((+())

sin(cos(=1/2(sin((+()+sin((-())

tg(=(2tg(/2)/(1-tg2(/2)

cos(=((1-sin2(=(1-tg2(/2)/(1+tg2(/2)

sin(=((1/1+ctg2(=(2tg(/2)/(1+tg2(/2)

cos((()=sin(sin(cos(cos(

sin(((((=sin(cos((sin(cos(

tg((+()=sin((+()/cos((+()=(tg(+tg()/(1-tg(tg()

tg((-()=(tg(-tg()/(1+tg(tg()

ctg((+()=(ctg(ctg(-1)/(ctg(+ctg()

ctg((-()=(ctg(ctg(+1)/(ctg(-ctg()

sin2(=2sin(cos(=(2tg()/(1+tg2()

cos2(=cos2(-sin2(=(1-tg2()/(1+tg2()=2cos2(-1=1-2sin2(

tg2(=2tg(/(1-tg2()ctg2(=(ctg2(-1)/2ctg(

ctg2(=(ctg2(-1)/2ctg(

cos2(/2=1+cos(/2cos2(=(1+cos2()/2

sin2(/2=1-cos(/2sin2(=(1-cos2()/2

cos(/2=((1+cos(/2

sin(/2=((1-cos(/2

tg(/2=((1-cos(/1+cos(=(sin()/(1+cos()=(1-cos()/sin(

ctg(/2=((1+cos(/1-cos(=sin(/(1-cos()=(1+cos()/sin(

sin(+cos(=(2 cos((/4-()

sin(-cos(=(2 sin((-(/4)

cos(-sin(=(2 sin((/4-()

cos(+cos(=2cos((+()/2cos((-()/2

cos(-cos(=-2sin((+()/2sin((-()/2

sin(+sin(=2sin((+()/2cos((-()/2

sin(-sin(=2sin((-()/2cos((+()/2

tg((tg(=(sin(((())/cos(cos(

cos(cos(=1/2(cos(((()+cos((+())

sin(sin(=1/2(cos(((()-cos((+())

sin(cos(=1/2(sin((+()+sin((-())

tg(=(2tg(/2)/(1-tg2(/2)